The Face of Battle - Keegan, John, 1934-2012 (London Jonathan Cape, 1982)
The Face of Battle is military history from the battlefield: a look at the direct experience of individuals at 'the point of maximum danger'. It examines the physical conditions of fighting, the particular emotions and behaviour generated by battle, as well as the motives that impel soldiers to stand and fight rather than run away. And in his scrupulous reassessment of three battles, John Keegan vividly conveys their reality for the participants, whether facing the arrow cloud of Agincourt, the levelled muskets of Waterloo or the steel rain of the Somme.
Include Maps, Bibliography and Index
Keywords: Waterloo, Battle of (Belgium : 1815) -- Battle